Psalms 1-50 - Saleska, Timothy E (Saint Louis : Concordia Publishing House, 2020)
"This scholarly volume in the Concordia Commentary series covers Psalms 1-50. The author devotes meticulous attention to the grammar, structure, and literary artistry of these Hebrew poems. The exposition of each psalm includes textual notes on the Hebrew and commentary in two parts. The first part analyzes the flow of thought, emotions, and theological beliefs of the poet. The second part interprets the psalm within the larger context of the Old Testament and also the New Testament, attesting the same faith held by Christians in the Gospel of Jesus Christ. It takes into consideration the history of interpretation and provides devotional applications to the individual and corporate life of prayer, trusting in God's eschatological salvation"--
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries